CORRELATION BETWEEN CHARACTERISTICS WITH HEAVY METAL CHROMIUM (Cr) LEVELS IN URINE OFMETAL COATING WORKERS IN SIDOARJO EAST JAVA INDONESIA - Ningrum, Nurul Fauziah (International Journal of Psychosocial Rehabilitation, 2020)
Metal coating process involves several chemicals, one of them is chromium. Chromium plating workers have a high risk of chromium exposure. The effects of chromium on health include carcinogenicity, immune system disorders, nervous system disorders, kidney disorders and damage, effects on breathing.sthe research analyzed the correlationbetween characteristics (age, working period, use of PPE masks, and use of PPE gloves) with heavy metal chromium (Cr) levels in urine on metal coating workers in Candi DistrictSidoarjothis was an observational descriptive research with cross sectional design. The sample number of metal coating workers was 15 people. Chromium levels in the urine of workers were analyzed by the laboratory with Atomic Absorption Spectrophotometry (AAS). Analysis of descriptive data analysis used coefficient contingency to determine the strength of the correlation between variables. showed that as many as 53% of workers had chromium levels in urine that exceeded the normal range. The results of the cross tabulation of the characteristics of respondents with chromium levels in urine of workers showed that there was a correlation between age and chromium levels in urine with a coefficient contingency value of 0.447. The correlationbetween working period above 10 years with chromium levels in urine with coefficient contingency value of 0.478. The use of Personal Protective Equipment (PPE) masks had a coefficient contingency value of 0.259 and the use of gloves with chromium levels in urine had a coefficient contingency value of 0.225. of this research was production workers had higher chromium levels in urine than non-production workers. The strength of the correlationbetween characteristics with chromium levels in the urine of workers was the working period with a moderate level of strength of the correlation. It is advisable to exercise control over waste management and compliance with the use of appropriate PPE, especially masks and gloves for workers.